2019
DOI: 10.1038/s41586-019-1620-6
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and genomic landscape of CD8+ T cells undergoing hepatic priming

Abstract: B. performed experiments on HBV-infected patients, analysed data, prepared the figures and edited the manuscript; C.B. and F.G. analysed the expression of genes involved in IL-2 sensing on KCs; A.C. and L.N. generated the lentiviral vectors encoding IL-2; G.G.-A. generated recombinant adeno-associated viruses; W.V.B. and D.D.P. generated rLCMV vectors; M.K., R.O. and L.G.G. provided funding, conceptual advice and edited the manuscript; M.I. designed and coordinated the study, provided funding, analysed the dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
193
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(221 citation statements)
references
References 71 publications
4
193
1
Order By: Relevance
“…In addition to T FH and Tregs, antiviral responders were also enriched for an intrahepatic M1 macrophage transcriptional signature. Mouse models have recently identified a central role for hepatic macrophages (Kupffer cells) in effective CD8 + T cell priming in the liver (22,23). For example, studies in an adoptive transfer model demonstrated that Kupffer cell-derived CXCL13 facilitates organization of CD8 + T cells, CD4 + T cells (including T FH ) and B cells in the liver, and that these lymphoid structures support intrahepatic immune priming (14,22).…”
Section: Accepted Articlementioning
confidence: 99%
“…In addition to T FH and Tregs, antiviral responders were also enriched for an intrahepatic M1 macrophage transcriptional signature. Mouse models have recently identified a central role for hepatic macrophages (Kupffer cells) in effective CD8 + T cell priming in the liver (22,23). For example, studies in an adoptive transfer model demonstrated that Kupffer cell-derived CXCL13 facilitates organization of CD8 + T cells, CD4 + T cells (including T FH ) and B cells in the liver, and that these lymphoid structures support intrahepatic immune priming (14,22).…”
Section: Accepted Articlementioning
confidence: 99%
“…T cell clustering was also observed in other anatomical sites, such as the liver [152]. Priming by Kupffer cells leads to the formation of dense, extravascular clusters of immotile cells and the development of effector cells.…”
Section: Regulation Of Effector Responsesmentioning
confidence: 83%
“…Indeed, a beneficial effect of PD-1 blockade on therapeutic vaccination is observed in the LCMV mouse model and in woodchucks infected with HBV (101,102). Moreover, HBV-specific T cells that were induced by dendritic cells are more responsive to PD-1 blockade when compared to those T cells primed by hepatocytes in HBV replication-competent transgenic mice (103). These synergistic effects did, however, not results into a clinical benefit in a small pilot study that administered nivolumab and a therapeutic vaccine to ten virally suppressed chronic HBV patients (83).…”
Section: Therapeutic Vaccinesmentioning
confidence: 99%